WIRELESS COMMUNICATIONS IN A TREE CANOPY - Pobsook Sooksumrarn; Chainarong Kittiyanpunya; Paiboon Yoiyod; Monai Krairiksh (My University, 2013)
The wireless communications in a tree canopy is essential for pre-harvesting control of fruit productions. To e-ciently communicate between a sensor node and a sink node, channel characteristics in a tree canopy must be well-established. In this paper, propagation channel characteristics at the frequencies of 2.45 and 5.2GHz have been estimated for designing a wireless communication system in a tree canopy. The proposed solution is based on measured path loss, time-varying signal strength and Angle of Arrival (AoA) for various paths in a tree canopy to estimate the channel. Since the waves re∞ect, refract, difiract and scatter from the foliage, it is complicated to flnd the true travelling path between a transmitter and a receiver at the nodes. The AoA estimator is used for physical interpretation of the channel. The experimental results demonstrate the channels in a tree canopy are mostly matched with the General Extreme Value model. The measured path gains illustrate that the appropriate antenna patterns must be selected to enhance the reliability of the system.
Keywords: Tree (set theory); Tree canopy; Millimeter-Wave Propagation and Modeling